DOES BASAL CELL CARCINOMA ARISING IN YOUNGER PATIENTS HAVE A MORE INVASIVE BEHAVIOR THAN THAT ARISING IN OLDER POPULATION? - H. A. Nikpour (Acta Medica Iranica, 2005)
There is an impression that basal cell carcinomas (BCC) occurring in younger population may be of more invasive behavior in comparison to those arising in older patients. The purpose of this study was to investigate this hypothesis by comparing the histological types of BCC in a large cohort of young and old patients. A total of 287 histological reports and clinical records were evaluated. A consecutive series of 95 patients less than 45 years old were compared with a consecutive series of 192 patients over 45 years of age. Tumors were classified according to the accepted definition of aggressive (morpheic, infiltrative and micronodular) and less aggressive (nodular and superficial) histological growth patterns. Aggressive growth types were found in 32% of patients over 45 and 29% of patients under 45, a difference which was not significant. There was a higher rate of incomplete excision in younger patients and this was highly significant (17% compared to 5%, P < 0.01). This study found that BCCs arising in young patients are not histologically different from those found in the older population. Clinically observed aggressive behavior of BCC in young patients may result from inadequate surgical excision due to cosmetics and diagnostic doubt.